1998
DOI: 10.2337/diabetes.47.3.381
|View full text |Cite
|
Sign up to set email alerts
|

13C/31P NMR studies on the mechanism of insulin resistance in obesity.

Abstract: The mechanism of insulin resistance in obesity was examined in ten obese (BMI 33 +/- 1 kg/m2) and nine lean (BMI 22 +/- 1 kg/m2) Caucasian women during a hyperglycemic-hyperinsulinemic clamp using 13C and 31P nuclear magnetic resonance (NMR) spectroscopy to measure rates of muscle glycogen synthesis and intramuscular glucose-6-phosphate (G-6-P) concentrations. Under similar steady-state plasma concentrations of glucose (approximately 11 mmol/l) and insulin (approximately 340 pmol/l), rates of muscle glycogen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 0 publications
11
63
0
2
Order By: Relevance
“…Phosphorous NMR has been used to study effects of insulin (and of IR) on levels of glucose-6-phosphat e in skeletal muscle. By magnifying the subtraction (insulin¡basal) NMR spectrum of muscle phosphorous, it has been found that in healthy volunteers insulin causes increased G-6-P and this is blunted in IR (11,13,14). This supports the concept that IR derives from defects at glucose transport and/or phosphorylation.…”
Section: Non-pet Methods For Investigation Of Skeletal Muscle Glucosesupporting
confidence: 65%
See 1 more Smart Citation
“…Phosphorous NMR has been used to study effects of insulin (and of IR) on levels of glucose-6-phosphat e in skeletal muscle. By magnifying the subtraction (insulin¡basal) NMR spectrum of muscle phosphorous, it has been found that in healthy volunteers insulin causes increased G-6-P and this is blunted in IR (11,13,14). This supports the concept that IR derives from defects at glucose transport and/or phosphorylation.…”
Section: Non-pet Methods For Investigation Of Skeletal Muscle Glucosesupporting
confidence: 65%
“…NMR spectroscopy has been shown to be a very powerful tool for investigating glucose metabolism in vivo (9). It is very useful for the study of the synthesis and degradation of glycogen in muscle (9)(10)(11)(12)(13). Phosphorous NMR has been used to study effects of insulin (and of IR) on levels of glucose-6-phosphat e in skeletal muscle.…”
Section: Non-pet Methods For Investigation Of Skeletal Muscle Glucosementioning
confidence: 99%
“…In contrast to the results from the model of Randle and co-workers, which predicted that fat-induced insulin resistance would result in an increase in intramuscular glucose-6-phosphate, we found that the drop in muscle glycogen synthesis was preceded by a fall in intramuscular glucose-6-phosphate, suggesting that increases in plasma fatty acid concentrations initially induce insulin resistance by inhibiting glucose transport or phosphorylation activity, and that the reduction in muscle glycogen synthesis and glucose oxidation follows. The reduction in insulin-activated glucose transport and phosphorylation activity in normal subjects maintained at high plasma fatty acid levels is similar to that seen in obese individuals, 16 patients with type 2 diabetes, 5,6 and lean, normoglycemic insulin-resistant offspring of type 2 diabetic individuals. 7,8 Hence, accumulation of intramuscular fatty acids (or fatty acid metabolites) appears to play an important role in the pathogenesis of insulin resistance seen in obese patients and patients with type 2 diabetes.…”
Section: Fatty Acid-induced Muscle Insulin Resistancementioning
confidence: 49%
“…Whereas this study evaluated data from rodents, we have some reason to believe that it may be applicable to human subjects as well. Specifically, even under experimentally induced conditions of hyperglycemia and hyperinsulinemia, healthy human subjects never displayed a Ͼ2-fold increase in [G6P] (12,33,34,36,37), suggesting the importance of G6P homeostasis in human skeletal muscle. Given the delicacy of the system's homeostatic balance, it is surprising that it does not seem to be substantially disrupted in patients with non-insulin-dependent diabetes (NIDDM) or genetic, obesity, and lipid-induced insulin resistance (IR) (12,33,34,37).…”
Section: Role Of Insulin-stimulated Proportional Activation In Maintamentioning
confidence: 99%